2021
DOI: 10.2147/ijgm.s343110
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index (SII) Can Be an Early Indicator for Predicting the Severity of Acute Pancreatitis: A Retrospective Study

Abstract: Objective: Systemic immune-inflammation index (SII) is a new systemic inflammatory prognostic indicator associated with outcomes in patients with different tumors. Studies have shown an association between SII and many chronic/acute inflammatory diseases. This study aimed at exploring whether SII can be used as an effective parameter for predicting the severity of acute pancreatitis (AP). Methods: A total of 101 acute pancreatitis patients were enrolled in this study (mild acute pancreatitis (MAP): n = 73 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The SII, which brings together three inflammatory peripheral cell counts including neutrophils, lymphocytes, and platelets, is increasingly considered a readily available biomarker for systemic inflammation ( 20 , 35 , 36 ). It can better reflect the body’s immune and inflammatory states than any aforementioned markers in isolation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SII, which brings together three inflammatory peripheral cell counts including neutrophils, lymphocytes, and platelets, is increasingly considered a readily available biomarker for systemic inflammation ( 20 , 35 , 36 ). It can better reflect the body’s immune and inflammatory states than any aforementioned markers in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…It can better reflect the body’s immune and inflammatory states than any aforementioned markers in isolation. Previous studies have found that the SII has an important role in predicting the prognosis of patients with some physical diseases, such as tumors, cerebral infarction, cardiovascular disease, and acute pancreatitis ( 18 , 20 , 21 , 36 ). As far as we know, there are few studies on the SII in psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been considered as a better index to reflect the local immune response and systemic inflammation. SII was first described as predictor for the prognosis of hepatocellular carcinoma ( 9 ), but it has been recently applied in inflammation-linked diseases such as acute pancreatitis and COVID-19 ( 12 , 13 ). During systemic inflammation, thrombocytosis and neutrophilia are considered responses to systemic inflammation, and lymphopenia predicts cellular immune injury.…”
Section: Discussionmentioning
confidence: 99%
“…SII can be used as an effective index to assess the degree of inflammation. For example, SII could effectively identify the severity of acute pancreatitis, outperformed NLR and PLR ( 12 ). Compared with mild COVID-19 patients, the severe had significantly higher SII value ( 13 ).…”
Section: Introductionmentioning
confidence: 99%